2008
DOI: 10.2165/00003495-200868020-00005
|View full text |Cite
|
Sign up to set email alerts
|

Guide to Drug Therapy for Lower Urinary Tract Symptoms in Patients with Benign Prostatic Obstruction

Abstract: The relationship between erectile dysfunction (ED) and lower urinary tract symptoms (LUTS) caused by benign prostatic obstruction (BPO) has recently gained increasing attention. Both BPO and ED are highly prevalent in older men and both conditions frequently contribute to a reduction in overall quality of life. Current medical treatment of LUTS/BPO consists of monotherapy with alpha(1)-adrenoceptor antagonists or 5alpha-reductase inhibitors, a combination of these two agents or, in some cases, various phytothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 123 publications
0
9
0
1
Order By: Relevance
“…Although both types of therapeutic approaches have proven effective for improving urinary flow, they are not effective for all men and can produce adverse effects that require termination of the therapeutic regimen. Moreover, LUTD can become refractory to this therapeutics [5], [6]. There is a need to explore other targets for therapeutics that might provide relief from LUTD with improved tolerability and duration.…”
Section: Introductionmentioning
confidence: 99%
“…Although both types of therapeutic approaches have proven effective for improving urinary flow, they are not effective for all men and can produce adverse effects that require termination of the therapeutic regimen. Moreover, LUTD can become refractory to this therapeutics [5], [6]. There is a need to explore other targets for therapeutics that might provide relief from LUTD with improved tolerability and duration.…”
Section: Introductionmentioning
confidence: 99%
“…Los mecanismos potenciales implicados incluyen una deficiencia de ó xido nítrico, hiperactividad autonó mica, aumento de la actividad Rho-cinasa y de la endotelina y, finalmente, la aterosclerosis pé lvica 59 (fig. 2).…”
Section: Papel De Los Alfa-bloqueantes En El Tratamiento De La Prostaunclassified
“…Numerous studies have demonstrated that LUTS is associated with ED in men, independent of age or general health. The RhoA/Rho‐kinase pathway is involved in the mechanism of LUTS‐associated ED [95]. The action of several factors in addition to noradrenaline (e.g., ET‐1, Ang II) are likely involved in increased smooth muscle activity in both LUTS/BPH and sexual dysfunction, and are dependent on Rho‐kinase activity [96].…”
Section: Rho‐kinase Pathway In Male Genital Organsmentioning
confidence: 99%